﻿A new Arthrinium-like genus of Amphisphaeriales in China - Ning Jiang; Hermann Voglmayr; Chun-Yan Ma; Han Xue; Chun-Gen Piao; Yong Li (MycoKeys, 2022)
Species of Arthrinium s. l. are usually known as endophytes, pathogens or saprobes occurring on various hosts and substrates and are characterised by globose to subglobose, sometimes irregular, dark brown and smooth-walled or finely verruculose conidia, always with a truncate basal scar. Currently, Arthrinium s. l. contains two phylogenetically distinct clades, namely, Apiospora and Arthrinium s. s. However, Arthrinium trachycarpi and Ar. urticae have still not been properly classified. With new isolates from diseased leaves of Lithocarpus glaber collected in China, we propose the new Arthrinium-like genus Neoarthrinium in Amphisphaeriales. Based on the morphology and phylogeny of multiple loci, the new genus is established with the type species, N. lithocarpicola and three new combinations, N. moseri (syn. Wardomyces moseri), N. trachycarpi (syn. Ar. trachycarpi) and N. urticae (syn. Ar. urticae) are added to this genus.